THE STATUS OF DEPUTY MINISTER WITHIN THE CIVIC SYSTEM OF REPUBLIC OF INDONESIA - Aidin ,SH (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Theoretically,  the basic concept of the appointment of vise minister is to develop the effectiveness and efficiency of the execution of the state ministerial functions. In advance,  the constitution of Indonesia did not recognize the existence of vise minister. According to the constitution,  the highest official in the state ministerial is on minister as the assistance of president. Nevertheless,  because of changes and complexity of state ministerial functions that it is considered necessary to appoint vise minister which is in charge to assist minister in performing his/her tasks and functions. It is a normative research. It uses both conceptual and statutory approach. It applies deductive method in analyzing research data. This research finds out that the authority of president to appoint vise minister has been stipulated in the Constitution of Republic of Indonesia of 1945 article 17 (1 and 2). In addition,  the appointment of vice minister also refers to the Law Number 39 of 2008 on the state ministerial about vise minister. It stipulates that vise minister is in charge to assist minister and responsible to minister and his appointment is only relied on the political interest of president.Keyword: vice minister